MALAYSIAN TOURISM INDUSTRY AND ITS INTERACTING FACTORS - Hamid, Junainah Abd Hamid; shukri, Sakinah mohd; shukri, Sakinah mohd (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to identifying important influential variables for attracting tourist of Iran in Malaysia, An empirical investigation. Tourism is considered an industry which can be highly profitable for nations and it can be viewed from a global perspective. The examination of this study in Malaysia interprets the image of the country which come from positive word of mouth has the most positive impact on Iranian tourists’. For the past few years a lot of Iranians came to Malaysia to visit the country recommended by their friends, relatives and families who are in Malaysia to study, and by a lot of Iranians who came to study in Malaysia. Cultural similarities, being a Muslim country, friendliness and hospitality of the Malaysians and the good quality of the universities and education have led to positive words of mouth. Those who visited the country recommend that their friends and families visit the country and it has become a favourite destination for Iranian tourists.